Immersive simulations with extreme teams. (August 2020) - Brown, Olivia; Power, Nicola; Conchie, Stacey M.
Extreme teams (ETs) work in challenging, high pressured contexts, where poor performance can have severe consequences. These teams must coordinate their skill sets, align their goals, and develop shared awareness, all under stressful conditions. How best to research these teams poses unique challenges as researchers seek to provide applied recommendations while conducting rigorous research to test how teamwork models work in practice. In this article, we identify immersive simulations as one solution to this, outlining their advantages over existing methodologies and suggesting how researchers can best make use of recent advances in technology and analytical techniques when designing simulation studies. We conclude that immersive simulations are key to ensuring ecological validity and empirically reliable research with ETs.